Teaching Experiences in Kampus Mengajar Batch 6: EFL Case Study at South Kalimantan Indonesia - Kamalia, Niska; Isnaniah; Yuliani, Novi Dwi (Universitas Nusantara PGRI Kediri, 2025)
This studywas conducted to explore and understand the experiences of students in joining and undergoing the Kampus Mengajar program at schools in South Kalimantan Province and their experience in teaching English during their participation on that program. This research employed a qualitative approach in case study method with twelve participants who were university students in South Kalimantan Province who took part in Kampus Mengajar Batch 6 Program. The main source of data was an online open-ended questionnaire within thirty-one questions and documentation in form of pictures from participants as evidence that related to the research information. The data were analysed by using the thematic analysis, using two theories; the Experiential Learning Theory and Adult Learning Theory. The finding show that the program involved three preparatory stages, including registration, selection, and pre-assignment processes, before students were deployed to schools. Participants conducted school surveys to assess the condition of facilities, teacher quality, and student comprehension. While most participants did not encounter major challenges, those who did were able to develop both hard and soft skills. Regardless of their academic backgrounds, the participants displayed strong enthusiasm for teaching English and used creative methods to enhance student engagement. The program enabled them to apply their academic knowledge in real teaching environments, contributing over three hours of instruction per week. The data revealed that most of the respondents identified the substantial positive effects of Kampus Mengajar Batch 6, particularly in stimulating change in students' literacy and numeracy skills. Meanwhile, the program encouraged substantial contributions to the Indonesian education system, with the respondents asserting transformative influences on their professional development as well as on the institutional capacity of partner schools.